2009
DOI: 10.1097/scs.0b013e31819b97ef
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Endoscopic Sinus Surgery on Sleep Quality in Patients With Chronic Nasal Obstruction Due to Nasal Polyposis

Abstract: Endoscopic sinus surgery with polypectomy significantly improves sleep quality, including snoring and daytime sleepiness in patients with chronic nasal obstruction due to nasal polyposis. However, it has a limited benefit on apnea-hypopnea index scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
2
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 15 publications
3
75
2
4
Order By: Relevance
“…Treatment of nasal congestion, however, has not been proven to improve sleep quality. The impact of rhinosinusitis treatment on OSA has been shown to be limited [41,42], and to date, there have been no published reports of the effect of OSA treatment on rhinosinusitis.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of nasal congestion, however, has not been proven to improve sleep quality. The impact of rhinosinusitis treatment on OSA has been shown to be limited [41,42], and to date, there have been no published reports of the effect of OSA treatment on rhinosinusitis.…”
Section: Discussionmentioning
confidence: 99%
“…Also, patients with CRSwNP have a twofold higher risk of suffering sleep disturbance compared with controls [7]. Poor sleep quality has been observed in patients with chronic rhinosinusitis and was improved after sinus surgery [8]; however, sinus surgery did not improve polysomnographic findings in patients with CRSwNP but increased their score on the Epworth Sleepiness Scale (ESS) [9]. On the other hand, there is no report in the literature which simultaneously evaluates both polysomnography (PSG) and Pittsburgh Sleep Quality Index (PSQI) in patients with CRSwNP.…”
Section: Introductionmentioning
confidence: 97%
“…A number of studies have reported the association of nasal blockage with daytime sleepiness [8,9] and improvement in daytime with relief of nasal obstruction [28]. A unique feature of our study was that we have assessed the chance of sleepiness with nasal blockage for each of the eight items in Epworth Sleepiness Scale.…”
Section: Discussionmentioning
confidence: 96%